2014
DOI: 10.1073/pnas.1402262111
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of IRON-REGULATED TRANSPORTER 1 (IRT1) to the plant-soil interface plays crucial role in metal homeostasis

Abstract: In plants, the controlled absorption of soil nutrients by root epidermal cells is critical for growth and development. IRON-REGULATED TRANSPORTER 1 (IRT1) is the main root transporter taking up iron from the soil and is also the main entry route in plants for potentially toxic metals such as manganese, zinc, cobalt, and cadmium. Previous work demonstrated that the IRT1 protein localizes to early endosomes/trans-Golgi network (EE/TGN) and is constitutively endocytosed through a monoubiquitin-and clathrindepende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
246
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(262 citation statements)
references
References 56 publications
(70 reference statements)
9
246
1
1
Order By: Relevance
“…Although homologs of most ESCRT 0-III complex components occurring in yeast and mammals are found in the Arabidopsis genome (Barberon et al, 2014;Hurley and Emr, 2006), the functions of only a few of these homologs have been explored. Among these homologs, Arabidopsis FYVE1, which has been predicted to act as a subunit of ESCRT-I (a PI3P-binding protein that is located on late endosomes), is the most studied (Barberon et al, 2014;Hurley and Emr, 2006;Gao et al, 2014;Gao et al, 2015). FYVE1, also termed FREE1 (FYVE domain protein required for endosomal sorting 1), is essential for plant growth due to its role in MVB (Multivesicular Bodies) biogenesis and membrane-protein sorting in cells (Gao et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although homologs of most ESCRT 0-III complex components occurring in yeast and mammals are found in the Arabidopsis genome (Barberon et al, 2014;Hurley and Emr, 2006), the functions of only a few of these homologs have been explored. Among these homologs, Arabidopsis FYVE1, which has been predicted to act as a subunit of ESCRT-I (a PI3P-binding protein that is located on late endosomes), is the most studied (Barberon et al, 2014;Hurley and Emr, 2006;Gao et al, 2014;Gao et al, 2015). FYVE1, also termed FREE1 (FYVE domain protein required for endosomal sorting 1), is essential for plant growth due to its role in MVB (Multivesicular Bodies) biogenesis and membrane-protein sorting in cells (Gao et al, 2014).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…FYVE1, also termed FREE1 (FYVE domain protein required for endosomal sorting 1), is essential for plant growth due to its role in MVB (Multivesicular Bodies) biogenesis and membrane-protein sorting in cells (Gao et al, 2014). FYVE1 acts as a crucial modulator of iron-regulated transporter1 (IRT1)-dependent metal transport and metal homeostasis by regulating the endosomal recycling of IRT1 back to the plasma membrane (Barberon et al, 2014). Additionally, a study of FREE1 implied the possibility of crosstalk between the ESCRT machinery and autophagy (Gao et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(5). In addition, a recent study also demonstrated the function of FREE1/FYVE1 in regulating the polarization of iron-regulated transporter 1 (IRT1) to the plant-soil interface, and the IRT1-dependent metal homeostasis in plant (17). FREE1 is essential for plant growth and FREE1 depletion causes seedling lethality (Fig.…”
mentioning
confidence: 95%
“…The dominant genes responsible for these processes were first cloned from Arabidopsis (Arabidopsis thaliana), known as the ferric-chelate reductase oxidase gene FRO2 and the Fe-regulated transporter gene IRT1 (Eide et al, 1996;Robinson et al, 1999). The expression of both genes is induced by Fe deficiency and is tightly regulated at multiple levels (Connolly et al, 2002(Connolly et al, , 2003Barberon et al, 2011Barberon et al, , 2014Shin et al, 2013;Ivanov et al, 2014).…”
mentioning
confidence: 99%